Moderation of Assessment in Transnational Higher Education - Wallace, M.; Mahmud, S.; Sanderson, G.; Yeo, S.; Briguglio, Carmela; Hukam-Singh, P. (Australian International Education Conference 2010, 2010)
This paper fills a gap in literature on TNE practices by reporting the preliminary findings from a research study on moderation of assessment inTNE involving Australian universities and their offshore partner institutions. The research project, funded by the Australian Learning and Teaching Council (AL TC) investigates processes that ensure fair and equitable assessment both before it is administered and after it has been completed, viewing moderation as a quality assurance and quality control measure. Overall, our research aims to collate moderation-related information, develop a transnational community of practice through the research framework and create a critically negotiated framework of inclusive practice for moderation of assessment in TNE settings resulting in an online, downloadable toolkit available to universities.